Effectiveness of Hiit Compared to Moderate Continuous Training in Improving Vascular Parameters in Inactive Adults - Garcia-Hermoso, A (BioMed Central Ltd., 2019)
Background: Strong evidence shows that physical inactivity increases the risk of many adverse health conditions, including major non-communicable diseases, such as cardiovascular disease (CVD), metabolic syndrome, and breast and colon cancers, and shortens life expectancy. We aimed to determine the effects of moderate (MCT)- versus high-intensity interval training (HIT) on vascular function parameters in physically inactive adults. We hypothesized that individualized HIT prescription would improve the vascular function parameters more than the MCT in a greater proportion of individuals. Methods: Twenty-one inactive adults were randomly allocated to receive either MCT group (60-75% of their heart rate reserve, [HRR] or HIT group (4 min at 85-95% of peak HRR), 3 days a week for 12 weeks. Vascular function (brachial artery flow-mediated dilation, FMD [%], normalized brachial artery flow-mediated dilation, FMDn [%], aortic pulse wave velocity, PWV [m·s - 1 ], AIx, augmentation index: aortic and brachial [%]), were measured at baseline and over 12 weeks of training. In order for a participant to be considered a responder to improvements in vascular function parameters (FMDn and PWV), the typical error was calculated in a favorable direction. Results: FMD changed by - 1.0% (SE 2.1, d = 0.388) in the MCT group, and + 1.8% (SE 1.8, d = 0.699) in the HIT group (no significant difference between groups: 2.9% [95% CI, - 3.0 to 8.8]. PWV changed by + 0.1 m·s - 1 (SE 0.2, d = 0.087) in the MCT group but decreased by - 0.4 m·s - 1 in the HIT group (SE 0.2, d = 0.497), with significant difference between groups: - 0.4 [95% CI, - 0.2 to - 0.7]. There was not a significant difference in the prevalence of no-responder for FMD (%) between the MCT and HIT groups (66% versus 36%, P = 0.157). Regarding PWV (m·s - 1 ), an analysis showed that the prevalence of no-responder was 77% (7 cases) in the MCT group and 45% (5 cases) in the HIT group (P = 0.114). Conclusions: Under the conditions of the present study, both groups experienced changed in vascular function parameters. Compared to MCT group, HIT is more efficacious for improving FMD and decreasing PWV, in physically inactive adults. Trial registration: ClinicalTrials.gov NCT02738385 registered on 23 March 2016. © 2019 The Author(s).